Impact of Digitalization on Select Banks - Kotishwar, A. (Indian Journal of Finance, 2018)
An economy is said to be cashless where the transaction of money is in the digital form other than cash. Demonetization brought a massive radical change in the transaction mode in the general public, and the positive side to it is our nation took a greater leap towards a cashless economy. The present study focused on the impact of technology on select banks with respect to transactions pertaining to online digital transactions and their contribution towards business per employee of respective banks and to assess the impact of 3G/4G communication technology on select banks with respect to transactions pertaining to credit and debit cards, NEFT, RTGS, mobile phone based transactions, and ECS and their contribution towards business per employee of respective banks.